An investigation of functional quality characteristics and water interactions of navy bean, chickpea, pea, and lentil flours. Issue 1 (8th January 2022) - Tas, Ozan; Ertugrul, Ulku; Grunin, Leonid; Oztop, Mecit Halil
Abstract: Legume flours are great sources of protein, dietary fiber, starch, minerals, and vitamins. In recent years, the utilization of different legume flours in food systems has gained attention due to their sustainable and functional properties. This study aimed to characterize and examine the water interactions of different legume flours: navy bean, chickpea, pea, and lentil. For this purpose, in addition to the standard techniques (proximal analysis, Fourier transform infrared, protein solubility, and water solubility/absorption index), time‐domain nuclear magnetic resonance (TD‐NMR) relaxometry was also performed to explain the molecular interactions in the flours. Based on the results, carbohydrate and protein content of legume flours varied from 67.44 to 72.23 (g/100 g dw) and 23.19 to 27.03 (g/100 g dw) with low fat (0.86–5.44 [g/100 g dw]) and moisture content (6.01–8.14 [g/100 g dw]). Despite the slight differences in their compositions being small, moisture, protein, and carbohydrate contents influenced flour–water interactions. Thus, flour–water mixtures were assessed, and findings showed that water solubility index (WSI) followed the order: chickpea > lentil > navy bean > pea, whereas water absorption index (WAI) followed the order: pea > navy bean > lentil > chickpea. T2 relaxation times measured by NMR and protein solubility results were also in accordance with these results. The results of this study demonstrated that legume flours that were investigated offered potential for commercial applications. Because various food applications require different flour–water interactions, a suitable flour can be selected by considering these results. Abstract : In this study, four different legume flours (navy bean, chickpea, pea, and lentil) were characterized. Furthermore, the interactions of these flours with water were presented and discussed.